2016
DOI: 10.1159/000447058
|View full text |Cite
|
Sign up to set email alerts
|

Photochemotherapy of Cutaneous Graft-versus-Host Disease May Reduce Concomitant Visceral Disease

Abstract: Background: Photochemotherapy may be used to treat cutaneous graft-versus-host disease (GvHD). Animal models show that in the days after photochemotherapy and antigen provocation, cells with an antigen-specific suppressive phenotype are elicited in the lymphoid organs. In GvHD, host antigens are present not only in the skin treated by photochemotherapy but also in the visceral tissues. Objective: The aim of this paper was to evaluate the effect on visceral acute GvHD (aGvHD) of photochemotherapy of the skin. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This is supported by our previous report of patients with acute GVHD both in the skin and viscera, where the time to treatment by photochemotherapy after acute-GVHD diagnosis was a median 21 days (interquartile range 12-28, min.-max. 1-43 days), in the group of patients who reached CR of acute GVHD of the liver and the gastrointestinal channel, a CR that was associated with conditioning with TBI and long-term survival [27]. In the present report, no adverse synergy of TBI on tumor immunity was found.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This is supported by our previous report of patients with acute GVHD both in the skin and viscera, where the time to treatment by photochemotherapy after acute-GVHD diagnosis was a median 21 days (interquartile range 12-28, min.-max. 1-43 days), in the group of patients who reached CR of acute GVHD of the liver and the gastrointestinal channel, a CR that was associated with conditioning with TBI and long-term survival [27]. In the present report, no adverse synergy of TBI on tumor immunity was found.…”
Section: Discussionsupporting
confidence: 49%
“…In mice, photochemotherapy may suppress DTH in the skin distant from the area treated, and this distant effect may be blocked by ketanserin, an unspecific serotonin inhibitor, which blocks the migration of not only mast cells [25], but also the dendritic cell migration and T-cell priming [26]. Yet, the systemic effect of photochemotherapy remains disputed, and the mediation thereof is not clearly chartered, but we have found that photochemotherapy of the skin may suppress acute GVHD of the internal organs in patients who had received total body irradiation (TBI) [27]. The experimental acute-GVHD reaction and the DTH reaction may both elicit effector cells within a week [28], and a week is what is needed to induce GVL in animal models [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…PUVA not only interferes with DNA synthesis and affects fibroblast activity (Cruz, Guecheva, Bonato, & Henriques, 2012; Wang, Liu, Gu, & Zhang, 2011), but also scavenges ROS through malate dehydrogenase (MD), succinate dehydrogenase (SD), and ubiquitin oxidoreductase thereby protecting normal cells. In general, photochemotherapy represented by PUVA is one of the more effective ways to treat skin diseases (Feldreich, Ringden, Emtestam, & Omazic, 2016).…”
Section: Pharmacological Effects Of Xanthotoxinmentioning
confidence: 99%
“…However, the evidence are limited to retrospective studies or case reports (LoE IV), thus there are no phototherapy guidelines for these dermatoses. [67][68][69][70][71][72]…”
Section: Other Dermatosesmentioning
confidence: 99%